Effect of Health Education on Environmental Health on Changes in Health Behavior in Students at SDN 1 Sembulung, Cluring District, Banyuwangi - Gufron Wahyudi; Febrika Devi Nanda; Rahmawati Raharjo (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
According to the 2020 Indonesian Health Profile, the coverage of SD/MI schools that provide health services in Indonesia in 2020 is 84.7%. There are 2 provinces with the highest coverage that have provided health services, namely DKI Jakarta and Central Kalimantan. The province with the lowest coverage of SD/MI schools providing health services is Papua (11.9%). Aim of this research is to know influence of health education about environmental health to healthy lifestyle student of SDN 1 Sembulung. This research used pre experiment design by using Equivalent Time Sample Design. Population of the research was 101 respondents who are class student 4,5,6 at SDN 1 Sembulung Banyuwangi and sample 50 respondents were sampled using Quota Sampling. Data collection used questionnaire after participating in health education or not and then the data was tasted using Chi Square test.Result of the research indicated that most students have less behavior 92% but not give health education 7 of 25or 28%.Who have good behavior and statistical result sig 5% with (df) I and show that 0.000 < 0.05 or 21.33 > 3.84 so Ho rejected Ha accepted.It means there is influence of health education about environmental health to healthy lifestyle student of SDN 1 Sembulung Cluring Banyuwangi. Therefore, health education on healthy lifestyle behavior can be enhanced to make good healthy lifestyle behaviors. In an effort to change the health behaviors of students author provides health education about environmental health, and creating a clean and healthy lifestyle. And supporting the clean Friday program implemented by the Regent Banyuwangi.